Kitab Sunan Ad-Darimi: Perspektif Biografi, Sistematika dan Penilaian Ulama - Muhammad Tohir Ritonga (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
This study aims to describe how the biography of life and systematics of the book of Ad-Darimi Sunan and describes how the scholar's assessment of Sunan's book is related. This study uses descriptive qualitative research methods with a library survey approach, i.e. research supported by literature related to the research problem. The results of the study showed that the biography and systematics of the book of Sunan Ad-Darimi took a thought that the Imam ad-darimi was believed as a great scholar, so many learned to him about Religion especially the issue of Hadith. Among those listening to his ceremony were the Imam al-Bukhari, Muslim, Abu Dawud, at-Tirmizi who were all older than him, while the scholar's assessment of the Sunan ad-darimi is one of the nine main books of the Hadith, despite all the praises, sanjungan as well as positive assessments submitted by the scholars to the Imam Ad-daraimi, that there were also some weak stated hadiths, mursal, mauquf, maktu ', even munkar in the book. The results of this research are expected to be able to contribute to science to us to better know the personalities and the works of previous scholars in particular in the field of hadith.